IS THE FEMALE OFFENDER HERE? THE WOMAN QUESTION IN ARTICLES ABOUT DRUG TRAFFICKING IN A BRAZILIAN JOURNAL OF CRIMINAL SCIENCES - Braga, Ana Gabriela Mendes [UNESP]; Ferreira, Letícia Cardoso [UNESP] (FapUNIFESP (SciELO), 2023)
This work aims to map and discuss the representations constructed around the female offender in a Brazilian Criminal Sciences journal, as well as to demarcate absences of this category, using a feminist legal method. For this, we used the documentary analysis, cutting a sample composed of articles from the Brazilian Journal of Criminal Sciences published in the last twenty years with the theme of the illicit trade in narcotics. The material was read through the content analysis technique, directed by Katharine Bartlett's proposal in Feminist Legal Methods. In the end, in the context of a growing increase on women's criminalization and in the interest on this theme, we conclude that, although the female offender category is present in most of the sample, it was mobilized more descriptively - for the composition of a scenario - than as an analytical category, by the reflexivity on gender and crime.
A criminosa está aqui? A pergunta pela mulher em artigos sobre tráfico de drogas de uma revista de Ciências Criminais brasileira
Keywords: Criminal Sciences; drug trafficking; female criminality; Female offender; feminist legal method